Welfare state reform in Southern Europe : fighting poverty and social exclusion in Italy, Spain, Portugal and Greece - Ferrera, Maurizio (Routledge, 2005)
This new study delivers a detailed analysis of the efforts being made to reduce poverty and social exclusion in Portugal, Spain, Italy and Greece. After an initial discussion of the 'southern model' of the welfare state, the situation of each country is clearly illustrated. This book also discusses how the experience of southern Europe might bear upon the situation of the East European accession countries. This is excellent reading for those interested in social change across Europe and beyond.
Keywords: Europe, Southern -- Social policy.; Welfare state -- Europe, Southern.; Human services -- Europe, Southern.; Marginality, Social -- Europe, Southern.; Europe méridionale -- Politique sociale.; État providence -- Europe méridionale.; Services sociaux -- Europe méridionale.; POLITICAL SCIENCE -- Public Policy -- Social Services & Welfare.; SOCIAL SCIENCE -- Human Services.; Human services; Marginality, Social; Social policy; Welfare state; Southern Europe